Loss of LaMATE impairs isoflavonoid release from cluster roots of phosphorus‐deficient white lupin. Issue 3 (16th August 2021) - Zhou, Yaping; Olt, Philipp; Neuhäuser, Benjamin; Moradtalab, Narges; Bautista, William; Uhde‐Stone, Claudia; Neumann, Günter; Ludewig, Uwe
Abstract: White lupin ( Lupinus albus L.) forms brush‐like root structures called cluster roots under phosphorus‐deficient conditions. Clusters secrete citrate and other organic compounds to mobilize sparingly soluble soil phosphates. In the context of aluminum toxicity tolerance mechanisms in other species, citrate is released via a subgroup of MATE/DTX proteins (m ultidrug a nd t oxic compound e xtrusion/d et ox ification). White lupin contains 56 MATE/DTX genes. Many of these are closely related to gene orthologs with known substrates in other species. LaMATE is a marker gene for functional, mature clusters and is, together with its close homolog LaMATE3, a candidate for the citrate release. Both were highest expressed in mature clusters and when expressed in oocytes, induced inward‐rectifying currents that were likely carried by endogenous channels. No citrate efflux was associated with LaMATE and LaMATE3 expression in oocytes. Furthermore, citrate secretion was largely unaffected in P‐deficient composite mutant plants with genome‐edited or RNAi ‐silenced LaMATE in roots. Moderately lower concentrations of citrate and malate in the root tissue and consequently less organic acid anion secretion and lower malate in the xylem sap were identified. Interestingly, however, less genistein was consistently found in mutant exudates, opening the possibility that LaMATE is involved in isoflavonoid release.